Is the Cure Worse than the Disease? County-Level Evidence from the COVID-19 Pandemic in the United States - Catalina Amuedo-Dorantes; Neeraj Kaushal; Ashley N. Muchow (Institute of Labor Economics (IZA), 2020)
Using county-level data on COVID-19 mortality and infections, along with county-level information on the adoption of non-pharmaceutical interventions (NPIs) in the United States, we examine how the speed of NPI adoption affected COVID-19 mortality. Our estimates suggest that advancing the date of NPI adoption by one day lowers the COVID-19 death rate by 2.4 percent. This finding proves robust to alternative measures of NPI adoption speed, model specifications that control for testing and mobility, and across various samples: national, restricted to the Northeast region, excluding New York, and excluding the Northeast region. We also find that the adoption speed of NPIs is associated with lower infections, as well as lower non-COVID mortality, suggesting that these measures slowed contagion and the pace at which the healthcare system might have been overburdened by the pandemic. Finally, NPI adoption speed appears to have been less relevant in Republican counties, suggesting that political ideology might have compromised their efficiency.
Keywords: I1; I10; I18; 330; COVID-19; mortality; infections; non-pharmaceutical interventions; United States